Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1590/s1806-37132005000500004
|View full text |Cite
|
Sign up to set email alerts
|

Fatores preditivos da evolução da asma aguda em crianças

Abstract: Objective: To use clinical and functional characteristics observed upon admission to an emergency room to identify factors predictive of the occurrence and course of acute asthma attacks in children. Methods: We prospectively studied 130 asthmatic children, from 1 to 13 years of age, who were treated for acute asthma attacks in an emergency room, evaluating status determined at admission and over the course of the crisis. Clinical scores were determined and arterial oxygen saturation by pulse oximetry was meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
(52 reference statements)
0
2
0
Order By: Relevance
“…Contradicting this conclusion, we found the recent report by Paro and Rodrigues, (6) who evaluated 130 children from one to thirteen years of age with acute asthma in São Paulo. Studying predictive factors of hospital admissions due to asthma, these authors reported that arterial oxygen saturation and clinical scores obtained at the beginning of the emergency treatment were useful but found that PEF measurement did not contribute to predicting hospitalization.…”
Section: Editorialmentioning
confidence: 93%
“…Contradicting this conclusion, we found the recent report by Paro and Rodrigues, (6) who evaluated 130 children from one to thirteen years of age with acute asthma in São Paulo. Studying predictive factors of hospital admissions due to asthma, these authors reported that arterial oxygen saturation and clinical scores obtained at the beginning of the emergency treatment were useful but found that PEF measurement did not contribute to predicting hospitalization.…”
Section: Editorialmentioning
confidence: 93%
“…The variables evaluated were age, sex, weight, height, serum magnesium dosage, presence of adverse events, presence of pneumonia, use of antibiotics, clinical evolution through the modified Wood–Downes severity score (Figure 1). The outcomes analyzed were length of stay in the pediatric emergency, need for admission to a pediatric ward or pediatric ICU (PICU), use of ventilatory support and death 20,21 …”
Section: Methodsmentioning
confidence: 99%